Nanosecond level time synchronization in datacenter network based on Telemetry architecture - Qianli ZHANG; Chaofan ZHANG; Jilong WANG; Xiangyu TANG; Zhengchen SHEN; Hui WANG (Tongxin xuebao)
To solve the problems of the traditional local time synchronization architecture being disconnected from centralized management, requiring extra interaction overhead, meanwhile with less time data susceptible to outliers, the nanosecond level time synchronization system was proposed based on Telemetry for the high-precision time synchronization requirements of data center networks.Combined with the outlier factor detection algorithm, timestamp information within the background traffic of the data center was collected, the large amount of time information reported was processed and analyzed, and a centralized automatic synchronization with nanosecond level precision was eventually achieved, which was convenient for subsequent global network scheduling.The proposed system was implemented and evaluated on the programmable switch.Experimental results show that between multiple hops and at different link rates, the nodes can achieve high-precision time synchronization at the nanosecond level.